The Effect of Aerobic Exercise on Improving SleepQuality and Flexibility in Overweight Women in the Covid-19 Pandemic Era - Widanita, Neva; Anggraeni, Dewi (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2023)
This study aims to determine the effect of aerobic exercise on improving sleep quality and anxiety in overweight women in the era of the COVID-19 pandemic. Physical activity is needed following aerobic exercise To maintain body fitness and ideal body shape. This research is a single-group pretest-posttest experimental study. The subjects in this study were overweight women aged 25-55, with 47 respondents. The measurement instruments in this study were the PSQI and the Sit and Reach Test. The data analysis technique used the normality test with the Kolmogorov-Smirnov test, the homogeneity test using the Levene test, and the significance test using a paired t-test. The results of the analysis of this study indicate that the results of the PSQI t-test (13.858) are greater than the t-table and the results of the t-count flexibility (-12.786), so aerobic exercise is effective in improving sleep quality and flexibility in overweight women in Purwokerto